Qualitative Evaluation of a Toddlers’ Speech Delay Early Detection Poster - Sheba, Shiane Hanako; Arum, Euis Reliyanti; Ekasari, Tetty (International Journal of Ethno-Sciences and Education Research, 2023)
The estimated number of 0 to 4-years-old children with speech disorders in Indonesia is 1.3 million people. If they are not treated properly, they will have serious consequences in adulthood. The Ministry of health of Indonesia has launched a speech disorder detection in The Child Development Monitoring Programs carried out by Posyandu cadres or Community Health Center officers. To support the program, a poster design for the early Detection of Speech Disorders in Toddlers (DeGabbi) has been created. Prior to dissemination, it is necessary to evaluate the effectiveness of the poster by conducting qualitative research. FGDs with toddlers’ mothers and posyandu cadres were conducted using an open interview guideline regarding the message, the language, and the appearance of the poster. Triangulation was carried out on Puskesmas officers, media design experts, and Indonesian language experts. Prior to the FGD, informants were asked to look at Degabbi's poster on the room wall for 5 minutes. Results of the FGD showed that all informants understood the poster messages that stated, "Whether the child is a speech delay or not at this age." Regarding the contents of the poster, one informant stated that could not understand the foreign terms, and another informant suggested to add arrows as a flow guide. Concerning the appearance, one informant thought it was better to use a stiffer material and increase the poster size. The triangulation on media design experts provided feedback relating to the images, layout, and flow of posters, while Indonesian language experts provided feedback on the diction of substitute words for foreign terms and the more effective sentences and phrases. After knowing the weaknesses of the DeGabbi poster, it then will be corrected. The DeGabbi poster is expected to be an effective and have leverage for early detection of speech disorders.